Elevated CO2 affects kelp nutrient quality: A case study of Saccharina japonica from CO2‐enriched coastal mesocosm systems. Issue 1 (14th December 2020) - Zhang, Xiaowen; Xu, Dong; Han, Wentao; Wang, Yitao; Fan, Xiao; Loladze, Irakli; Gao, Guang; Zhang, Yan; Tong, Shanying; Ye, Naihao
Abstract : Kelps provide critical services for coastal food chains and ecosystem, and they are important food source for some segments of human population. Despite their ecological importance, little is known about long‐term impacts of elevated CO2 (eCO2 ) on nutrient metabolites in kelps and the underlying regulation mechanisms. In this study, the kelp Saccharina japonica was cultured in CO2 ‐enriched coastal mesocosm systems for up to 3 months. We found that, although eCO2 significantly increased the growth rate, carbon concentrations, and C/N ratio of S. japonica, and it had no effect on total nitrogen and protein contents at the end of cultivation period. Meanwhile, it decreased the lipid, magnesium, sodium, and calcium content and changed the amino acid and fatty acid composition. Combining the genome‐wide transcriptomic and metabolic evidence, we obtained a system‐level understanding of metabolic response of S. japonica to eCO2 . The unique ornithine–urea cycle (OUC) and aspartate‐argininosuccinate shunt (AAS), coupled with TCA cycle, balanced the carbon and nitrogen metabolism under eCO2 by providing carbon skeleton for amino acid synthesis and reduced power for nitrogen assimilation. This research provides a major advance in the understanding of kelp nutrient metabolic mechanism in the context of global climate change, and such CO2 ‐induced shifts in nutritional value may induce changes in the structure and stability of marine trophic webs and affect the quality of human nutrition resources.